Intercultural competence in Higher Education: academics’ perspectives - Pinto, Susana (2018)
Purpose – The purpose of this study is to diagnose and understand Portuguese academics’ perspectives on the components of Intercultural Competence and on the importance of its development by higher education students. Design/methodology/approach – Academics’ perspectives were identified during two discussion and reflection sessions included in the overall training program Intercultural Competence in Higher Education: building proposals with academics that took place at a Portuguese public university. Data was collected through audio recordings of the two sessions and observation notes, and was subject to content analysis drawing on Deardorff’s Process Model of Intercultural Competence (2006). Findings – Academics recognize the multidimensionality of intercultural competence, acknowledging it comprises attitudes (acceptance and respect; curiosity and openness), knowledge (others’ cultural contexts; self-knowledge and cultural self-awareness) and skills (observation and listening) that altogether will lead to individuals’ desired internal and external outcomes. The development of intercultural competence by higher education students, regarded in close relation to higher education internationalization, is considered crucial for changing prejudiced attitudes, preparing students to live in a global world, and empowering them professionally. Originality/value – The study sheds light on an issue that has been insufficiently addressed by research: academics’ perspectives on intercultural competence development, namely in the Portuguese higher education context.